Psikoedukasi Psikologi Positif: Sebuah Intervensi “Grit” pada Siswa SMA X di Tangerang - Marganel, Brendha; Ilyas, Putri Ardhiyyah Muammar; Justine, Leticia; Hidayat, Ivana Tatiana; Khong, Zorryhazel; Novanto, Yusak (Bahasa Indonesia, 2025)
The transition period from high school to university level is a critical time for individual development among students, particularly to begin the emerging adulthood period. The aim of implementing the Grit Up! 2024 is to measure the effectiveness of the "grit" psychoeducation program in preparing high school students to face the challenges of the study period, especially in terms of adaptation and academic achievement area. The psychoeducation program uses presentation methods and group activities. This program was evaluated by using a pre-test-post-test evaluation design. The results used Wilcoxon and Mann-Whitney statistical analysis to determine differences in grit levels based on gender and understanding of the material. The result of the study shows there’s a difference in level of understanding from the students before and after the program. On the other side, the result also shows there’s no significant difference in grit level based on gender differentiation. The Grit Up! psychoeducational program 2024 has succeeded in increasing students' motivation and understanding of the importance of grit. For further researchers, it is recommended to use measuring instruments specifically designed for academic purposes, implement them in different cultural backgrounds, and design further training for teachers and parents.   Abstrak Masa transisi dari sekolah menengah atas ke jenjang universitas merupakan masa krusial bagi perkembangan individu siswa, terutama untuk memulai masa dewasa awal. Tujuan pelaksanaan Grit Up! 2024 adalah untuk mengukur efektivitas program psikoedukasi "grit" dalam mempersiapkan siswa sekolah menengah atas menghadapi tantangan masa studi, terutama dalam hal adaptasi dan pencapaian akademik. Program psikoedukasi ini menggunakan metode presentasi dan aktivitas kelompok. Program ini dievaluasi dengan desain evaluasi pra-tes-pasca-tes. Hasilnya menggunakan analisis statistik Wilcoxon dan Mann-Whitney untuk menentukan perbedaan tingkat grit berdasarkan gender dan pemahaman materi. Hasil penelitian menunjukkan adanya perbedaan tingkat pemahaman siswa sebelum dan sesudah program. Program psikoedukasi Grit Up! 2024 telah berhasil meningkatkan motivasi dan pemahaman siswa tentang pentingnya grit. Di sisi lain, hasil penelitian juga menunjukkan tidak adanya perbedaan yang signifikan dalam tingkat grit berdasarkan diferensiasi gender. Bagi peneliti selanjutnya disarankan untuk menggunakan alat ukur yang dirancang khusus untuk keperluan akademis, melaksanakan di latar belakang budaya yang berbeda, dan merancang pelatihan lanjutan bagi guru dan orang tua.